2001
DOI: 10.1016/s1573-5214(01)80017-8
|View full text |Cite
|
Sign up to set email alerts
|

Enset (Ensete ventricosum (Welw.) Cheesman) kocho yield under different crop establishment methods as compared to yields of other carbohydrate-rich food crops

Abstract: The kocho yield of enset, in terms of weight and energy, under different crop establishment methods, was investigated at Areka Research Centre, southern Ethiopia, and compared with the yields of other main starch crops grown in the country. The maximum fresh weights of kocho after fermentation from enset plants transplanted once (Tl), twice (T2) or thrice (D) were 25.9,54.1 and 37.1 kg plant-I, respectively. When yield was expressed per unit of space and time, the maximum fresh yields of fermented kocho (70% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 5 publications
3
94
0
Order By: Relevance
“…The advantage of combining crop and livestock activities in the traditional systems was related to the availability of cheap fodder for livestock, such as enset leaves, and of animal manure, contributing to enset and coffee growth. In the traditional home gardens, livestock also played a critical role in providing a protein and nutrient rich diet to the household, given the low nutritious value of enset (Brandt et al 1997;Tsegaye and Struik 2001). The transition towards khat cultivation reduced herd sizes due to decreased fodder availability, especially from enset, and also lowered the interest in livestock rearing as a source of cash and manure.…”
Section: Farming System Transitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The advantage of combining crop and livestock activities in the traditional systems was related to the availability of cheap fodder for livestock, such as enset leaves, and of animal manure, contributing to enset and coffee growth. In the traditional home gardens, livestock also played a critical role in providing a protein and nutrient rich diet to the household, given the low nutritious value of enset (Brandt et al 1997;Tsegaye and Struik 2001). The transition towards khat cultivation reduced herd sizes due to decreased fodder availability, especially from enset, and also lowered the interest in livestock rearing as a source of cash and manure.…”
Section: Farming System Transitionsmentioning
confidence: 99%
“…4). Enset leaves have a high protein content (Brandt et al 1997;Tsegaye and Struik 2001;Solomon et al 2008) and a feeding value that is comparable to a good quality grass (Fekadu and Ledin 1997). Similarly, Kandari et al (2014) reported a decline in per capita herd size following complete replacement of major fodder crops by khat in Harar region of eastern Ethiopia.…”
Section: Farming System Transitionsmentioning
confidence: 99%
See 3 more Smart Citations